2022
DOI: 10.3390/ijerph19116540
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dewatering of Activated Sludge by Skeleton-Assisted Flocculation Process

Abstract: Sludge dewatering is the fundamental process of sludge treatment. Environmentally friendly and efficient sludge conditioning methods are the premises of sludge to achieve dehydration reduction and resource utilization. In response to sewage plant sludge dehydration, fly ash (FA), polymerized aluminum chloride (PAC), and polymer sulfate (PFS) were studied separately to determine their sludge dehydration performance, and the effects of these three conditioner composite regulations on sludge dehydration propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…These values are similar to the effects of PIX 113 sludge conditioning at a dose of approximately 2.0-6.0 mL/L (0.13-0.40 g/g DS). For comparison, Xi et al [57] showed that the use of flu ash in sludge conditioning at a dose of 10-15 g/g DS allows obtaining SRF = 1.03 × 10 11 m/kg and FH = 74%. However, to achieve very low hydration of the dewatered sludge of 68%, a dose of 30 g/g DS was necessary.…”
Section: Research Results-combinationmentioning
confidence: 99%
“…These values are similar to the effects of PIX 113 sludge conditioning at a dose of approximately 2.0-6.0 mL/L (0.13-0.40 g/g DS). For comparison, Xi et al [57] showed that the use of flu ash in sludge conditioning at a dose of 10-15 g/g DS allows obtaining SRF = 1.03 × 10 11 m/kg and FH = 74%. However, to achieve very low hydration of the dewatered sludge of 68%, a dose of 30 g/g DS was necessary.…”
Section: Research Results-combinationmentioning
confidence: 99%
“…Studies have shown that the larger the D50 (the particle size corresponding to a sample with a cumulative particle size distribution of 50%), the better for sludge dewatering. Xia et al [17] used fly ash in conjunction with polymeric iron sulfate and polymeric aluminum chloride to treat residual sludge and showed that the flocs of the original sludge were relatively fluffy. The addition of complex conditioning agents can neutralize the negative charge on the surface of the flakes and reduce the repulsion between colloidal ions, making it easier for the flakes to collide and aggregate, thereby forming flocculated particles with large particle size and dense structure.…”
Section: Sludge Particle Sizementioning
confidence: 99%